2021
DOI: 10.1002/pds.5192
|View full text |Cite
|
Sign up to set email alerts
|

SGLT‐2 inhibitors and the risk of hospitalization for community‐acquired pneumonia: A population‐based cohort study

Abstract: Purpose: Sodium-glucose co-transporter 2 inhibitors (SGLT-2i) have been associatedwith an increased risk of genitourinary tract infections. Through similar biological mechanisms, they may also increase the risk of community-acquired pneumonia. Our objective was to compare the rate of hospitalization for community-acquired pneumonia (HCAP) with SGLT-2i compared to dipeptidyl peptidase-4 inhibitors (DPP-4i) among patients with type 2 diabetes.Methods: We used the United Kingdom's Clinical Practice Research Datal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…In a meta-analysis of nine randomised controlled trials, SGLT-2 inhibitors were associated with a trend towards a reduced risk of new onset of chronic obstructive pulmonary disease (risk ratio 0.79, 0.61 to 1.02). 51 Furthermore, large observational studies and a meta-analysis of cardiovascular outcome trials have associated SGLT-2 inhibitors with a decreased risk of pneumonia, 10 11 52 a condition that often leads to chronic obstructive pulmonary disease exacerbations. The mechanisms behind heterogeneous findings of SGLT-2 inhibitors preventing severe but not moderate chronic obstructive pulmonary disease exacerbations are unclear and should be explored further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of nine randomised controlled trials, SGLT-2 inhibitors were associated with a trend towards a reduced risk of new onset of chronic obstructive pulmonary disease (risk ratio 0.79, 0.61 to 1.02). 51 Furthermore, large observational studies and a meta-analysis of cardiovascular outcome trials have associated SGLT-2 inhibitors with a decreased risk of pneumonia, 10 11 52 a condition that often leads to chronic obstructive pulmonary disease exacerbations. The mechanisms behind heterogeneous findings of SGLT-2 inhibitors preventing severe but not moderate chronic obstructive pulmonary disease exacerbations are unclear and should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Finally, although SGLT-2 receptors are not expressed in the lungs, these drugs may exert beneficial effects by reducing carbon dioxide retention by inducing glucosuria and by reducing the risk of pneumonia, a major precipitator of chronic obstructive pulmonary disease exacerbations. 9 10 11 12 To date, observational studies investigating the effects of these novel antihyperglycaemic drugs on respiratory disease exacerbations have been limited. 13 14 In one study, DPP-4 inhibitors were not associated with a decreased risk of severe exacerbation of chronic obstructive pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…A population-based cohort study provided reassuring evidence that SGLT2is were associated with a decreased rate of community-acquired pneumonia among patients with type 2 diabetes. 33 In this study, the mean baseline SLEDAI score of 4 suggested that these participants had only low-grade disease activity. No clinically meaningful changes in the SLEDAI score over time were observed.…”
Section: Discussionmentioning
confidence: 55%
“…With the exception of the most common genitourinary tract infections, sporadic studies have reported that SGLT2i was associated with skin and pulmonary infections [ 61 , 62 , 63 ]. Urticaria, pruritus, photosensitivity, and various rashes caused by SGLT2i may be driven by a potential skin toxicity [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urticaria, pruritus, photosensitivity, and various rashes caused by SGLT2i may be driven by a potential skin toxicity [ 61 , 62 ]. In addition, SGLT2i also led to an increased liquid glucose concentration of the airway surface, which translated directly to an increased proliferation of pathogenic bacteria and induced the occurrence of lung infections, for some SGLT2i bound with the SGLT-1 receptors in the lungs, such as canagliflozin and ipragliflozin [ 63 , 64 ]. Hence, we conducted further research to determine whether SGLT2i increased the risk of a potential extra-urogenital infection.…”
Section: Discussionmentioning
confidence: 99%